Participate in physical education preferences of boys and girls of secondary education through "the GR level of social participation in learning" Preferencias participativas en educaciòn física de los chicos y chicas de la educación secundaria mediante la "la escala de participación social en el aprendizaje - Isabel Rico Sánchez; José Luis Graupera Sanz; Luis Miguel Ruiz Pérez; Esmeralda Mata (Asociación Española de Ciencias del Deporte, 2010)
This investigation is concerned with the analysis of interaction preferences among secondary school children in physical education. 6.263 secondary school children participated in this study and completedthe Social Participation in Learning Scale (GR). Psychometric properties were re-evaluated and it wasanalyzed gender differences in the four dimensions of this scale: Cooperative dimension, Competitive dimension, Affiliative dimension and Individualistic dimension. The results showed that, in general,secondary school children think that they are cooperative, in reference to gender; boys got higher scoresin the competitive and individualistic dimensions and girls in the cooperative and affiliative dimensionsof the scale. The signification of these results is analyzed. KEY WORDS: Social Interaction, Gender, Assessment, Participation, Secondary physical education   El presente estudio analiza las preferencias participativas de los chicos y chicas de la ESO en EducaciónFísica. Participaron 6.263 escolares españoles en esta investigación a los que se les aplicó La escala GR de Participación Social en el Aprendizaje, con lo que se revalidó la utilidad y permitió establecer las diferencias de género. El análisis de las propiedades de medida de la escala ratifico su estructura compuesta de cuatro dimensiones: Competitiva, Cooperativa, Afiliativa e Individualista. Los resultados mostraron que globalmente fue la dimensión cooperativa la predominante entre los estudiantes participantes en este estudio. En cuanto a las diferencias de sexo, éstas fueron significativas en las cuatrodimensiones, siendo las puntuaciones más elevadas en las dimensiones cooperativa y afiliativa para laschicas, y mayores en las dimensiones competitivas e individualistas para los chicos. Se analiza elsignificado de estos resultados. PALABRAS CLAVE: Interacción social, Género, evaluación, participación, educación física secundaria.